IOT Based Waste Monitoring For Smart City (International Journal of Engineering and Computer Science, 2017)
The IOT is a new trend technology which includes different wireless connectivity like wi-fi, GSM, zigbee, Bluetooth .IOT that is internet of things which basically defines connecting things over wireless connectivity things are any physical quantity in day to day life which will need to be monitor. These quantity may be temperature, level, weight, pressure which impact on human activity these things are monitor control over wireless media. While using such system major focus on capability and system should make user friendly. Conventional wireless media is zigbee to get more capability and physical quantity which monitor is level. To enhance the smart city environment of such IOT based system it is essential to provide smart solution to become smarter. This paper is giving possible solution to make a city clean, hygiene, healthy in smart way.[1][2][6]